Home Visiting as an Equitable Intervention for Perinatal Depression: A Scoping Review - Tabb, Karen M.; Bentley, Brandie; Pineros Leano, Maria; Simonovich, Shannon D.; Nidey, Nichole; Ross, Kate; Huang, Wen-hao David; Huang, Hsiang (Frontiers in Psychiatry, 2022)
Abstract Objective: Maternal mental health disorders are a leading complication of childbirth. While few systems are adequately able to identify and treat depression, people experiencing perinatal depression may benefit from the intervention of home visiting. The intent of home visiting interventions is to alleviate stressors of parenthood for people facing additional risk factors. The aim of this scoping review is to investigate the effect of home visiting on perinatal depression grounded in published studies. Methods: We conducted a scoping review of the existing literature of studies relevant to perinatal depression and home visiting. We entered keywords in five search databases: MEDLINE, PsycInfo, CINAHL, Social Work Abstracts, and Google Scholar. All relevant literature published between January 1999 – December 2019 was reviewed. Duplicates, books, and errata were excluded from the study. As a scoping review, we included all studies published in English describing the inclusion of maternal depression in home visits. We hypothesize birthing people with perinatal depression will benefit from home visiting interventions. Results: The results from the scoping review and describe the use of home visiting to improve perinatal mental health. An initial 12,652 records were identified in the search. After duplicates were removed, the titles of 2,140 articles were assessed for applicability, however 29 identified for full-text eligibility and were included in this analysis. The majority of the studies included in this review were quantitative (n = 23), followed by qualitative (n=3), and mixed methods (n=3). Nearly all studies (n=28) using validated instruments such as the Edinburgh Postnatal Depression Scale to determine depressive symptoms. Discussion: This review offers preliminary qualitative insights on the efficacy of home visiting for administrating perinatal depression care. Studies show that home visiting programs can provide treatment for perinatal depression and reduce the effects of depression for birthing people. Our review suggests that the efficacy of home visiting programs beginning in the postpartum period are less predictable than prenatal home visiting intervention among various populations, including people experiencing both high-risk and low-risk situations. Keywords: Home Visiting, Depression, Perinatal, Postpartum